Neutrophil-to-lymphocyte ratio is superior to platelet-to-lymphocyte ratio as a prognostic predictor in advanced non-small-cell lung cancer treated with first-line platinum-based chemotherapy. (15th November 2018) - Guo, Dong; Li, Minghuan; Chen, Dawei; Jing, Wang; Zhu, Hui; Fu, Lei; Kong, Li; Yue, Jinbo; Yu, Jinming
Aim: We aimed to investigate the prognostic impact of the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in advanced non-small-cell lung cancer treated with first-line platinum-based chemotherapy and determine which of the two was a better predictor of prognosis.Materials & methods: We conducted multivariate Cox regression analysis to assess the independent effects of the NLR and PLR on patient survival.Results: In multivariate Cox regression analysis, the NLR was an independent risk factor predicting poor prognostic factor (HR: 2.464; 95% CI: 1.305–4.652; p = 0.005) and overall survival (HR: 1.954; 95% CI: 1.172–3.257; p = 0.01); however, the PLR was not a prognostic factor (progression-free survival; p = 0.105; overall survival; p = 0.239).Conclusion: The NLR was a better prognostic indicator than the PLR for advanced non-small-cell lung cancer treated with first-line platinum-based chemotherapy.